A Kirk Type Characterization of Completeness for Partial Metric Spaces - Romaguera, Salvador (Fixed point theory and applications (Hindawi Publishing Corporation), 2010)
We extend the celebrated result of W. A. Kirk that a metric space "Equation missing" is complete if and only if every Caristi self-mapping for "Equation missing" has a fixed point, to partial metric spaces.